Benzotriazine Di-Oxide Prodrugs for Exploiting Hypoxia and Low Extracellular pH in Tumors - Michael P. Hay; Hong Nam Shin; Way Wua Wong; Wan Wan Sahimi; Aaron T.D. Vaz; Pooja Yadav; Robert F. Anderson; Kevin O. Hicks; William R. Wilson (Molecules, 2019)
Extracellular acidification is an important feature of tumor microenvironments but has yet to be successfully exploited in cancer therapy. The reversal of the pH gradient across the plasma membrane in cells that regulate intracellular pH (pHi) has potential to drive the selective uptake of weak acids at low extracellular pH (pHe). Here, we investigate the dual targeting of low pHe and hypoxia, another key feature of tumor microenvironments. We prepared eight bioreductive prodrugs based on the benzotriazine di-oxide (BTO) nucleus by appending alkanoic or aminoalkanoic acid sidechains. The BTO acids showed modest selectivity for both low pHe (pH 6.5 versus 7.4, ratios 2 to 5-fold) and anoxia (ratios 2 to 8-fold) in SiHa and FaDu cell cultures. Related neutral BTOs were not selective for acidosis, but had greater cytotoxic potency and hypoxic selectivity than the BTO acids. Investigation of the uptake and metabolism of representative BTO acids confirmed enhanced uptake at low pHe, but lower intracellular concentrations than expected for passive diffusion. Further, the modulation of intracellular reductase activity and competition by the cell-excluded electron acceptor WST-1 suggests that the majority of metabolic reductions of BTO acids occur at the cell surface, compromising the engagement of the resulting free radicals with intracellular targets. Thus, the present study provides support for designing bioreductive prodrugs that exploit pH-dependent partitioning, suggesting, however, that that the approach should be applied to prodrugs with obligate intracellular activation.